Sosialisasi Hukum Perbankan: Pengenalan Umum Terkait Pinjaman Uang (Kredit) Bank: Pengabdian - Emmi Rahmiwita Nst; Risky Akbar Barus; Erlan Sitorus; Kiki Nur Aida; Sri Mariani; Andini Sagita Lasari; Shely Maimunah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The legal banking socialization program is an effort to enhance legal awareness and financial literacy among young generations, enabling them to understand the legal responsibilities involved in banking transactions, particularly in credit agreements. This activity was conducted at MAS Al-Washliyah Tanjung Balai with the aim of introducing the basic concepts of banking law, the rights and obligations of debtors, and the legal risks arising from default. The methods applied included material presentation, interactive discussions, and evaluation through simple questionnaires to measure the improvement of participants’ understanding. The results showed a significant increase in students’ comprehension regarding credit application procedures, the importance of reading contract terms, and awareness of legal consequences in credit agreements. The activity also fostered a critical, cautious, and responsible attitude in dealing with modern banking services. Therefore, this socialization contributed positively to shaping a legally aware, financially literate, and integrity-driven young generation in the digital banking era.